THE ROLE OF ALTRUISTIC AND HEDONIC VALUE IN INCREASING GREEN PURCHASE INTENTION: MEDIATION PRO - ENVIRONMENTAL BEHAVIOR - Diah Adestia (IAIN Surakarta, 2022)
The purpose of this study is to determine the direct and indirect effect of altruistic value and hedonic value on green purchase intention as well as the effect of pro-environmental behavior on green purchase intention. The population in this study were university students in Surakarta. Sampling used purposive sampling technique with a total of 105 respondents of university students in Surakarta who have been or are willing to use green cosmetic. Methods of data collection was done by distributing questionnaires. The test tool used SPSS v.23 with data analysis using Path Analysis (a combined model of multiple regression model and mediation model). The results of this study indicate that altruistic value has a positive and significant effect on pro-environmental behavior, altruistic value has a positive and significant effect on green purchase intention, hedonic value has a positive and significant effect on pro-environmental behavior, hedonic value has no positive and significant effect on green purchase intention, pro-environmental behavior has a positive and significant effect on green purchase intention. Pro-environmental behavior has been shown to mediate the effect of altruistic value on green purchase intention, pro-environmental behavior has been shown to mediate the effect of hedonic value on green purchase intention.